Investigating Immune and Vascular Mechanisms in Glaucoma - Henderson, Jeff (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2026)
Glaucoma is a group of optic neuropathies characterised by progressive retinal ganglion cell (RGC) degeneration. It is the leading cause of irreversible blindness worldwide, affecting upwards of 80 million people. Elevated intraocular pressure (IOP) is the only modifiable risk factor for the disease, and current treatments therefore focus on reducing IOP, most commonly with topical medications. However, these medications are suboptimal, as they do not address the underlying cause of IOP elevation, which is increased resistance to aqueous humour (AH) outflow through the conventional outflow pathway. Additionally, many patients respond inadequately, and adherence to long-term dosing schedules is often poor, thus limiting the effectiveness of these interventions. Surgical procedures are available for treatment resistant cases, but these are invasive and carry significant risk of complications. Importantly, existing treatments do not target the root cause of vision loss: RGC death. There is therefore a need both for new therapies that more effectively lower IOP by reducing conventional outflow resistance, and for neuroprotective strategies that directly prevent RGC degeneration. Progress in both of these areas has been limited by an incomplete understanding of the disease's pathophysiology. The first objective of this project, addressed in Chapter 3 was to determine whether modulation of inflammatory pathways in the anterior segment can alter AH outflow and therefore IOP in glaucoma. In DBA/2J mice, the anterior chamber displayed a pro- inflammatory profile with increased infiltration of activated myeloid-lineage cells, upregulation of the inflammasome receptors NLRP3 and AIM2, and elevated levels of IL- 1beta and IL-18. These findings are consistent with canonical inflammasome activation and loss of ocular immune privilege, suggesting that sterile inflammation contributes to elevated IOP in this model. Intracameral injection of canonical inflammasome effector cytokines produced opposing effects on outflow facility, with IL-18 reducing and IL-1beta enhancing outflow. Outflow facility was increased in Asc-/- mice relative to wild-type controls, indicating that under physiological conditions, canonical inflammasome activation decreases outflow facility. To assess the role of non-canonical signalling, caspase-11-deficient (Casp11-/-) mice were subjected to dexamethasone-induced ocular hypertension (OHT), developing higher IOP and reduced outflow facility relative to wild- type controls, indicating a potential protective role for caspase-11. Collectively, thesefindings establish inflammation as a modulator of AH outflow and highlight the canonical inflammasome as potential therapeutic target for lowering IOP. The second objective of this project, addressed in Chapters 4 and 5, was to determine whether retinal vascular dysfunction is a feature of glaucoma, its timing in relation to RGC loss, and underlying mechanisms. In Chapter 4, IOP, retinal vascular integrity, and retinal structure were examined in DBA/2J mice and in mice with dexamethasone-induced OHT. Fundus fluorescein angiography (FFA) revealed increased retinal vascular leakage in DBA/2J mice from 6 months of age, coinciding with inner retinal thinning on optical coherence tomography (OCT), while dexamethasone-treated mice showed increased leakage after 4 weeks, preceding inner retinal thinning. These findings indicate that vascular leakage is an early consequence of OHT and may precede RGC degeneration. Immunostaining showed reduced Mfsd2a levels, but unchanged claudin-5 levels, in the inner retina of both models, implicating increased transcytosis as the mechanism of leakage. In Chapter 5, analysis of RNA-seq data from microbead OHT and optic nerve crush (ONC) models revealed Cav1 upregulation and transcriptional signatures of endothelial activation, inner blood-retinal barrier (iBRB) dysfunction, and innate immune activation in both models. These findings further highlight increased transcytosis and vascular dysfunction as common features of murine glaucoma and point to retinal inflammation as a mediating mechanism. In the microbead model, a biphasic inflammatory response was observed, with an early upregulation of innate immune signalling, an intermediate phase of partial resolution with vascular remodelling signatures, and a later resurgence of innate immune activation coinciding with RGC loss. The presence of vascular dysfunction signatures in the ONC model indicated that RGC degeneration itself can exacerbate vascular dysfunction, suggesting a self-reinforcing cycle of inflammation and vascular leakage once neurodegeneration is established. In summary, this thesis provides evidence that dysregulated inflammation and retinal vascular dysfunction contribute to the pathophysiology of glaucoma. It establishes sterile inflammation as a regulator of AH outflow and identifies the canonical inflammasome as a potential therapeutic target for IOP control. It also provides evidence that retinal vascular dysfunction is a common and potentially causal mediator of RGC loss across multiple models of glaucoma. Ultimately, this work supports the view of glaucoma as a systemic disease that leads to a loss of ocular homeostasis, rather than a disease of elevated IOP or RGC loss in isolation.
APPROVED
Keywords: Inflammation; Intraocular pressure; Glaucoma; Blood-retinal barrier